2018
DOI: 10.1021/jacs.8b04751
|View full text |Cite
|
Sign up to set email alerts
|

Conformationally Regulated Peptide Bond Cleavage in Bradykinin

Abstract: Ion mobility and mass spectrometry techniques are used to investigate the stabilities of different conformations of bradykinin (BK, Arg-Pro-Pro-Gly-Phe-Ser-Pro-Phe-Arg). At elevated solution temperatures, we observe a slow protonation reaction, i.e., [BK+2H]+H → [BK+3H], that is regulated by trans → cis isomerization of Arg-Pro, resulting in the Arg- cis-Pro- cis-Pro-Gly-Phe-Ser- cis-Pro-Phe-Arg (all- cis) configuration. Once formed, the all- cis [BK+3H] spontaneously cleaves the bond between Pro-Pro with perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
68
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(71 citation statements)
references
References 27 publications
3
68
0
Order By: Relevance
“…[20] This mechanism requires a cisconfigured peptide bond between the first and second residues (e.g., Xxx 1 -cis-Xxx 2 , where Xxx is any amino acid) -the same configuration that we assigned to a critical intermediate for cleavage of the peptide bond of bradykinin. [10] Capasso also found that cyclization of an Ala 1 -Pro 2 -NH 2 dipeptide has a significant pH dependence under more basic conditions, but was pH-independent in acidic conditions. [20] These results appear to be sequence dependent, as analysis of His 1 -Pro 2 -NH 2 cyclization produces a more bell-shaped pH dependence profile.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…[20] This mechanism requires a cisconfigured peptide bond between the first and second residues (e.g., Xxx 1 -cis-Xxx 2 , where Xxx is any amino acid) -the same configuration that we assigned to a critical intermediate for cleavage of the peptide bond of bradykinin. [10] Capasso also found that cyclization of an Ala 1 -Pro 2 -NH 2 dipeptide has a significant pH dependence under more basic conditions, but was pH-independent in acidic conditions. [20] These results appear to be sequence dependent, as analysis of His 1 -Pro 2 -NH 2 cyclization produces a more bell-shaped pH dependence profile.…”
Section: Introductionmentioning
confidence: 93%
“…Below, we show that subP undergoes sequential bond cleavages, producing both cyclo-Arg 1 -Pro 2 (cRP) and cyclo-Lys 3 -Pro 4 (cKP) in the form of DKPs. Similar to bradykinin, [10] the first cleavage is preceded by a configurationally-coupled protonation event. While the second cleavage involves only one charge state, a long induction period prior to cleavage is observed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quenching the reaction enables interrogation of these transient species captured in the MS instrument. [9] A mass spectrum collected 30 s after initiating the cleavage reaction is shown (Figure 3). Several satellite peaks are observed alongside the main charge state series, one of which corresponds to the enzyme substrate complex with a mass of 68,781 ± 2 Da, in agreement with dimeric M Pro bound to a single 11-mer substrate (1192 Da).…”
mentioning
confidence: 99%